Study And Evaluation of the Inhibitory Efficacy of Extracts of Sumbucus Nigra Flower and Tribulus Terrestris Fruits Against The Growth of Bacterial Species Isolated from Patients with Urinary Tract Infection (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted to isolate and diagnose the most important bacterial types causing urinary tractinfection from the inpatients and outpatients to Salah El Din General Hospital using routine isolation anddiagnosis methods. 70 samples were isolated, and the results showed two types of growth: Gram positivebacteria and Gram negative bacteria, where 10 bacterial types were isolated as follows:E. coli 42.85%, Kleibsiella. pneumonia 21.42% roteus mirabilis (11.42%), Staphylococcus aureus(7.14%), Enterobacter cloaca (5.71%), Serratia marcescens (2.85%), Pseudomonas aeruginosa (2.85%),Staphylococcus Saprophyticus. 2.85%, Micrococcus luteus 1.42%, and Citrobacter freundii 1.42%.The results of the susceptibility test for 9 types of antibiotics using the discs method showed a change inthe level of resistance to different antibiotics. The most effective antibiotics were Imipenem, Ciprofloxacinand Sulfamethoxaole. Plant extracts (both aqueous and alcoholic) of Sambucus nigra and Tribulus terrestrisfruits were used, and tested for their ability to inhibit the most isolated bacteria (E. coli , K. pneumonia P.mirabilis and S. aureus ). All alcoholic extracts were effective in the direction of Bacterial isolates, whileaqueous extracts, have little or no effect.
Keywords: Urinary Tract Infection, Antibiotics, Plant Extracts, Sumbucus nigra, Tribulus terrestris